The effectiveness of advance organizer on students' achievement in general college chemistry - Guanco, Hemogene R. (Animo Repository, 2001)
This study determines the measurable effects of the use of an Advance Organizer in teaching Chemistry 101. This study also determines the effect of the use of the advance organizer in the level of performance in chemistry among students of different cognitive levels. Two methods of teaching were used in the study, namely method of teaching Chemistry using Advance Organizer and the Traditional Lecture method. The effect of each method was measured in terms of the achievement of first year college Bachelor of Secondary education students who were taught selected topics in General College Chemistry using Advance Organizer. Specifically, this study determined significant differences in chemistry achievement: 1) of students who were taught using Advance Organizer and those who were taught without Advance Organizer, 2) among the students who are formal thinkers, early formal thinkers, and concrete thinkers who used the advance organizers, 3) of students of different cognitive levels under two methods of instruction. The interaction effect between methods of teaching and cognitive levels was also determined. A quasi-experimental design was employed in this study. Four intact classes composed of one hundred sixty (160) students enrolled in General College Chemistry at Northern Iloilo Polytechnic State College at Barotac Viejo and Estancia campuses were invited to participate in the study. A 75-item Chemistry achievement test developed by the researcher served as both pretest and posttest. The scores obtained by the students from the Test on Cognitive Development (TCD) determined the cognitive level of the subjects. (The data after which they were collected were then subjected to an Analysis of Covariance using the Unique Sum of Squares method, with pretest scores, high school grades in chemistry, and entrance test scores as covariates. The posttest score was used as the dependent variable.Results of the study revealed that 1) there is a significant difference (a=.05) in Chemistry achievement between students who were taught using the Advance Organizer and those who were taught using the traditional approach 2) there is no significant difference in the Chemistry achievement among students who are formal thinkers, early formal thinkers, and concrete thinkers using Advance Organizer 3) there is a significant difference in the Chemistry achievement of different cognitive levels of experimental and control groups and 4) there is no interaction effect between teaching methods and cognitive level of development of students. Based on the results of the study, it can be concluded that teaching chemistry concepts using Advance Organizer can facilitate meaningful learning and can enhance students' achievement in chemistry. It can also be concluded that the Advance Organizer method compared to the Traditional Lecture method, is a better method in teaching chemistry concepts.